Genetics and Clinical Characteristics of PPARγ Variant-Induced Diabetes in a Chinese Han Population - Gong, Siqian; Han, Xueyao; Li, Meng; Cai, Xiaoling; Liu, Wei; Luo, Yingying; Zhang, Si-min; Zhou, Lingli; Ma, Yumin; Huang, Xiuting; Li, Yufeng; Zhou, Xianghai; et al. (Frontiers in Endocrinology, 2021)
Objectives: PPARγ variants cause lipodystrophy, insulin resistance, and diabetes. This study aimed to determine the relationship between PPARγ genotypes and phenotypes and to explore the pathogenesis of diabetes beyond this relationship. Methods: PPARγ2 exons in 1002 Chinese patients with early-onset type 2 diabetes (diag-nosed before 40 years of age) were sequenced. The functions of variants were evaluated by in vitro assays. Additionally, a review of the literature was performed to obtain all reported cases with rare PPARγ2 variants to evaluate the characteristics of variants in different func-tional domains. Results: Six (0.6%) patients had PPARγ2 variant-induced diabetes (PPARG-DM) in the early onset type 2 diabetes group, including three with the p.Tyr95Cys variant in activation function 1 domain (AF1), of which five patients (83%) had diabetic kidney disease (DKD). Functional experiments showed that p.Tyr95Cys suppresses 3T3-L1 pre-adipocyte differ-entiation. A total of 64 cases with damaging rare variants were reported previously. Patients with rare PPARγ2 variants in AF1 of PPARγ2 had a lower risk of lipodystrophy and a higher rate of obesity than those with variants in other domains, as confirmed in patients identified in this study. Conclusion: The prevalence of PPARG-DM is similar in Caucasian and Chinese popula-tions, and DKD was often observed in these patients. Patients with variants in the AF1 of PPARγ2 had milder clinical phenotypes and lack typical lipodystrophy features than those with variants in other domains. Our findings emphasizing the importance of screening such patients via genetic testing and suggest that thiazolidinediones might be a good choice for these patients.